Whole-volume ADC histogram of the brain as an image biomarker in evaluating disease severity of neonatal hypoxic-ischemic encephalopathy - Wang, Ruizhu; Xi, Yanli; Yang, Ming; Zhu, Meijiao; Yang, Feng; Xu, Huafeng (Frontiers in Neurology, 2022)
ABSTRUCT To examine the diagnostic significance of apparent diffusion coefficient(ADC) histogram in quantifying neonatal hypoxic ischemic encephalopathy (HIE). An analysis was conducted on the MRI data of 90 HIE patients, 49 in the moderate-to-severe group, and the other in the mild group. The 3D Slicer software was adopted to delineate the whole brain region as the region of interest, 22 ADC histogram parameters were obtained. The interobserver consistency of the two radiologists was assessed by the interclass correlation coefficient (ICC). The difference of parameters (ICC>0.80) between two groups was compared by performing the independent sample t test or the mann-whitney U test. In addition, an investigation was conducted on the correlation between parameters and neonatal behavioral neurological assessment (NBNA) score. ROC curve was adopted to assess the efficacy of the respective significant parameter. Furthermore, the Binary Logistic regression was employed to screen out the independent risk factors for determining the severity of HIE.The ADCmean, ADCmin, ADCmax,10th-70th,90th percentile of ADC value of the moderate-to-severe group were smaller than those of the mild group, while the group’s variance, skewness, kurtosis, heterogeneity and mode-value were higher than those of the mild group(P<0.05). All the mentioned parameters, the ADCmean, ADCmin, and 10th-70th and 90th percentile of ADC displayed positive correlations with the NBNA score, mode-value and ADCmax displayed no correlations with the NBNA scroe, the rest showed negative correlations with the NBNA score(P<0.05). The area under the curve (AUC) of variance was the largest (AUC=0.977; cut-off 972.5, sensitivity 95.1%; specificity 87.8%). According to the Logistic regression analysis, skewness, kurtosis, variance and heterogeneity were independent risk factors for determining the severity of HIE(OR>1, P<0.05). The ADC histogram contributes to the HIE diagnosis and is capable of indicating the diffusion information of brain objectively and quantitatively. It refers to a vital method for assessing the severity of HIE.